Determining the minimal mulch film damage caused by the up-film transplanter. (March 2018) - Du, Sheng; Yu, Junzhi; Wang, Weibing
To satisfy the increasing demand for improving productivity while reducing pollution, this article proposes a method to determine the minimal mulch film damage in mechanical transplantation operations, which can be used to guide the design of all the up-film transplanters. Specifically, the whole working process of digging the hole for a typical dibble-type transplanter working in Xinjiang province of China is analyzed, in which the dibble motion serves to illustrate the effectiveness of the proposed method. Both the ideal condition and the realistic environmental force-involved condition are taken into consideration during analytically modeling the process of the mulch film damage. Based on the presented two-layer soil-layered model and basic motion principles, a series of equations is derived to describe the typical dibble-type transplanter motion involved gravity and soil counter-force. Furthermore, the derived relations between working parameters and structural parameters of the transplanter guide the search of a minimum value of the mulch film damage. Finally, simulation results verify the effectiveness of the presented theoretical calculation. More remarkably, the dibble motion in the preliminary field trial is similar to that in the simulations. The obtained results provide a new way to deal with the optimal design and operations of novel up-film transplanters.